Betty Fussell: The Story of Corn - Mason, Laura (Petits Propos Culinaires, 1993)
Betty Fussell: The Story of Corn: Alfred A Knopf, New York 1992: 356 pp, numerous b/w photographs and line drawings, index, selected bibliography, $30.00.